Development of Resistance Sintering Furnace for Heat Treatment of 22MnB5: Development of Resistance Sintering Furnace for Heat Treatment of 22MnB5 - Rashid, Mohd Fairuz; Abu Bakar, Hadzley; Hafizh, Hadyan; Adam, Abdul Aziz; Zamri, Mohd Najib (Journal of Sustainable Manufacturing in Transportation, 2022)
This paper presents the development of resistance heating furnace based on the direct electrical conduction method that can perform with lower energy. Based on the concept of resistance welding, resistance heating furnace was developed for heat treatment of 22MnB5 Boron steel with the aim to change the microstructure from pearlite to austenite phases before quenched into martensite phase. The main component for this machine consisted of transformer, copper electrodes, copper cable coil and wood frame structure. The design of the machine resembled resistance welding with upper and lower electrodes were assembled together mounted by the wood frame. The heating energy collected from the electrical current that flow through cooper cable that rolled through toroidal transformer. The result shows that the machine capable to heat the 22MnB5 Boron steel with maximum temperature of 721.2Â°C. However, the machine demonstrates overheat after 7 minutes due to the insulation burn of cooper cable. Further improvement of cooling system and copper insulation need to be addressed to prolong the heating operation.